(untitled) (Studia Prawnicze / The Legal Studies, 2023)
Autor artykułu porusza kontrowersyjne zagadnienie, zarówno w teorii jak i w praktyce, które stanowi centralne zagadnienie prawa międzynarodowego mianowicie instytucje odpowiedzialności państwa. Rozróżnia dwie podstawowe tendencje tj. konserwatywną i postępową, w którym ta pierwsza ogranicza odpowiedzialność państwa za szkody poniesione na jego terytorium przez cudzoziemca i sprowadza się tylko do obowiązku naprawienia szkody, w formie reparacji, druga natomiast, za akt agresji może obejmować akty przymusu. Autor opisuje ponadto proces kodyfikacyjny prawa międzynarodowego w zakresie odpowiedzialności państwa. The author of this article addresses a controversial issue, both in theory and in practice, which constitutes a central issue of international law, namely the institutions of state responsibility. He distinguishes two basic tendencies, i.e. a conservative one and a progressive one, in which the former limits the responsibility of a state for damage suffered on its territory by a foreign entity and comes down only to the obligation to repair the damage, in the form of reparations, while the latter, for an act of aggression, may include acts of coercion. The author further describes the codification process of international law on state responsibility.